Estimating potential surface water storage and captured sediment volumes in peatland restoration sites using drones - Wilson, Miles Perry (Drone systems and applications, 2025)
Peatland restoration addresses multiple United Nation’s Sustainable Development Goals and offers numerous ecosystem services. Quantifying surface water storage and captured sediment volumes of emplaced dams on restoration sites is highly desirable, for example as evidence to funders, but cannot be practically achieved with field surveys due to the number of sites and number of dams per site. In contrast, camera-equipped drones can efficiently capture high spatial resolution photographs of restoration sites which can be used to construct digital surface models, from which volumetrics can be calculated using Geographical Information Systems. This approach was demonstrated using a five-year repeat drone survey of a restoration site (~0.18 km2) containing 125 stone dams and 329 coir rolls. Stone dams and coir rolls were estimated to provide 248.0 m3 of potential surface water storage in July 2019, of which ~71% was filled by captured sediment by July 2024. Stone dams accounted for ~83% of potential surface water storage volume in 2019 and ~68% in 2024, as well as ~88% of the captured sediment. Efficiently quantifying surface water storage provides evidence to restoration funders with water-related interests and may help with the development of water-related credits/metrics as additional mechanisms to privately finance peatland restoration.